P08 Incidence of diagnosed dementia in the english longitudinal study of ageing in england: a 12-year follow-up. (2nd September 2017) - Cadar, D; Davies, H; Llewellyn, D; Batty, GD; Steptoe, A
Abstract : Background: There has been a suggestion that the incidence of dementia in England has recently declined. Crucially, however, these estimates have not been based on nationally representative samples. Accordingly, we calculated dementia incidence, the temporal trends and, additionally, examined various socioeconomic and geographical predictors of its occurrence. Methods: Data from the English Longitudinal Study of Ageing (ELSA), a prospective cohort study at baseline known to be representative of the English population, were used to investigate the rates of dementia incidence over seven waves between 2002 and 2014. Dementia was determined by doctor-diagnosis and the Informant Questionnaire on Cognitive Decline in the Elderly (score >3.38 indicative of dementia). Age- and sex-specific incidence rates of dementia were calculated for 5131 individuals aged 65 and older at study entry. Dementia incidence over time was examined by comparing age-specific incidence rates between two age-period-cohorts derived in ELSA using a median split in birth-year range (ELSA I: 1900–1925 and ELSA II: 1926–1950). The predictive value of education, wealth, geographical area, the index of multiple deprivations and the degree of urbanisation for dementia incidence were examined using Poisson regression. Dementia was determined by doctor-diagnosis and the Informant Questionnaire on Cognitive Decline in the Elderly (score >3.38 indicative of dementia). Age- and sex-specific incidence rates of dementia were calculated for 5131 individuals aged 65 and older at study entry. Dementia incidence over time was examined by comparing age-specific incidence rates between two age-period-cohorts derived in ELSA using a median split in birth-year range (ELSA I: 1900–1925 and ELSA II: 1926–1950). The predictive value of education, wealth, geographical area, the index of multiple deprivations and the degree of urbanisation for dementia incidence were examined using Poisson regression. Results: The average duration of follow-up was 7.7 years. As anticipated, there was a significant increase in the rates of dementia incidence with age, from 5.90 per 1000 person years at ages 65–69 to 31.59 at ages 85+. We observed an age-period-cohort effect on dementia incidence, with nearly 30% reduction in the incidence rates for participants of the same initial age group (75–79) at the study entry from ELSA I and II. Higher rates of dementia incidence were observed for London (Rate=15.52, Incidence rate ratio (IRR)=1.43 95% confidence intervals (CI) 1.01–2.03) compared with Northern England, and for those in the lowest wealth quintiles (Rate=14.61, IRR=2.18, 95% CI 1.55–3.06) compared with the highest. Conclusion: In a nationally representative sample, we observed a reduction in the age-specific dementia incidence over time. This incidence appeared to be patterned by group- and individual-level characteristics.